2009
DOI: 10.1177/1076029609335909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Activated Factor VII in Critical Bleeding: Clinical Experience of a Single Center

Abstract: Recombinant activated factor VII (rFVIIa) has been successfully used ''off-label'' in patients with refractory life-threatening hemorrhage. Intravenous rFVIIa was given to 31 patients unresponsive to standard therapy with blood products and surgical reexploration, who were bleeding due to trauma, surgery, organ transplantation, liver cirrhosis, ruptured uterus. We recorded their coagulation and hematologic profiles, acid-base balance, blood loss, number of red blood cells (RBC), plasma and platelet transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…20 Our review of the current literature and preclinical studies suggests that future management options may include the use of activated charcoal, hemodialysis, and administration of rFVIIa and/or PCC. 12,20 On the basis of the mean concentration differences, the mean fraction of dabigatran removed by dialysis was 62% at 2 hours and 68% at 4 hours. 15 In their own pharmaceutical insert, the manufacturer (Boehringer Ingelheim Pharmaceuticals) suggests the use of FFP and/or packed red blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Our review of the current literature and preclinical studies suggests that future management options may include the use of activated charcoal, hemodialysis, and administration of rFVIIa and/or PCC. 12,20 On the basis of the mean concentration differences, the mean fraction of dabigatran removed by dialysis was 62% at 2 hours and 68% at 4 hours. 15 In their own pharmaceutical insert, the manufacturer (Boehringer Ingelheim Pharmaceuticals) suggests the use of FFP and/or packed red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessing the risk of major bleeding complications have shown dabigatran to have a reduced amount of risk compared with other anticoagulants. 12,14,18,21 However, the lack of guidelines, protocols, and an established specific antidote to reverse the anticoagulation effect of dabigatran potentially increases morbidity and mortality in patients with CHI. Confronted with this new problem, we reviewed our initial clinical experience.…”
mentioning
confidence: 99%
“…Recombinant activated factor VII (rFVIIa; NovoSeven Âź , Novo Nordisk, Bagsvaerd, Denmark) 55 and prothrombin complex concentrates 56 can also be useful to rapidly reverse coagulopathy. However, there are no published clinical data on the use of these agents in patients receiving dabigatran and information is limited for the other new oral anticoagulants.…”
Section: Correct Clinical Use Of Dabigatranmentioning
confidence: 99%
“…As a result, it has been proposed that this agent may have potential in reversing the effects of a variety of anticoagulants, including the new oral thrombin inhibitors. It has been successfully used ''off-label'' in patients with refractory life-threatening haemorrhage [21].…”
Section: Management Of Bleeding In Acute Trauma Patientsmentioning
confidence: 99%